2022
DOI: 10.3329/sja.v20i1.60544
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol mediated drought stress impacts on germination, growth and accumulation of proline in rice (Oryza sativa L.)

Abstract: Drought is one of the major stress factors affecting the growth and development of plants, and is responsible for considerable crop yield losses worldwide. An experiment was conducted to compare three rice (Oryza sativa L.) varieties (BRRI dhan49, BRRI dhan71 and BRRI dhan75) for drought tolerance based on some growth parameters and physiological status in germination stage. Drought stress was imposed by five levels of polyethylene glycol (PEG) (0%, 10%, 15%, 20% and 25%). Rice varieties showed good germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…To simulate water deprivation stress, a PEG concentration of 25%, corresponding to -1215.9 kPa ( Stanley and Strey, 2003 ), reported as the maximal limit in previous studies in rice ( Islam et al., 2018 ; Sobahan et al., 2022 ) was used in this study. A preliminary test, conducted on the Lomello variety ( Supplementary Figure 2 ) using 15%, 20%, and 25% PEG, indicated that 25% PEG allowed a better distinction between primed and unprimed seeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To simulate water deprivation stress, a PEG concentration of 25%, corresponding to -1215.9 kPa ( Stanley and Strey, 2003 ), reported as the maximal limit in previous studies in rice ( Islam et al., 2018 ; Sobahan et al., 2022 ) was used in this study. A preliminary test, conducted on the Lomello variety ( Supplementary Figure 2 ) using 15%, 20%, and 25% PEG, indicated that 25% PEG allowed a better distinction between primed and unprimed seeds.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether these priming methods could aid rice seeds germinate better under water deprivation stress, polyethylene glycol (PEG) was used; this agent is widely used to regulate the osmotic potential due to the high hydrophilicity that allows it to sequester water molecules. Previous reports indicated PEG as an ideal system for germination screening due to its high molecular weight that prevents its entry through the plant cell walls while simulating water retention ( Islam et al., 2018 ; Sobahan et al., 2022 ). According to a 100-rice variety screening study ( Islam et al., 2018 ), as well as other more recent reports ( Sobahan et al., 2022 ), 25% PEG is considered the highest concentration that can be utilized for water stress simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sokoto & Muhammad, (2014), employing PEG up to a certain percentage will result in challenges for the radicle and plumule's appearance because of alterations in the gradient of the water potential between the seed's interior and the surrounding environment. The length of the radicle and plumule will decrease due to cell division and display under water stress conditions [23].…”
Section: Effect Of Peg On Radicle and Plumule Length Of Local Upland ...mentioning
confidence: 99%
“…Additionally, PEG with a high molecular weight (≥60,000) does not penetrate cell walls, making it an ideal material for simulating drought stress in plant cells and recreating soil-like conditions in vitro. Currently, PEG6000 has been widely used to simulate the effects of drought stress on plants in various aspects such as biochemical, physiological, metabolic, and photosynthetic studies [ 35 , 36 ]. In this work, DRPC chips were used to monitor the dynamic changes in cellular forces and cells’ viscoelastic moduli of both rice cells and rice protoplasts in real time under the treatments of varying concentrations of PEG6000 to simulate drought stress.…”
Section: Introductionmentioning
confidence: 99%